Integrasi Nilai Al-Ta'awun atau Gotong Royong dan Al-Ukhuwwah atau Persaudaraan dari Al-Qur'an dalam Membangun Model Kolaborasi dan Manajemen Komunitas Digital di Society 5.0 - Anwar Mukti; M. Luqman Hakim; Agung Mandiro Cahyono; Ahmad Nur Fathoni; Moh. Bahrudin Ana Asyifa Azzahro’ (Journal of Innovative and Creativity, 2021)
This study aims to examine the integration of Islamic values such as Al-Ta'awun (cooperation) and Al-Ukhuwwah (brotherhood) within digital collaboration and community management in the Society 5.0 era, grounded in the teachings of the Qur'an. The methodology includes qualitative and literature studies, alongside case analysis of Islamic boarding school curricula integrating Islamic values and digital technology. Findings reveal that applying ta'awun and ukhuwah values strengthens community collaboration and solidarity, while integrating technology in Islamic education enhances digital skills without compromising Islamic identity. This integration model supports the development of an inclusive and just society aligned with maqasid sharia principles and digital era challenges. The conclusion highlights that combining Islamic values with digital technology in community management and education offers an effective strategy to build an adaptive, ethical, and competitive society in the Society 5.0 era. Recommendations include strengthening technology-based teacher training and developing curricula responsive to digital advancements.